How can you write the expression with a rationalized denominator?See image
![How can you write the expression with a rationalized denominatorSee image class=](https://us-static.z-dn.net/files/d94/258947cfc4fdb4aae5fc60be2b4f31f9.png)
Okay, here we have this:
Considering the provided expression, we are going to rationalize the denominator, so we obtain the following:
[tex]\begin{gathered} \frac{\sqrt[3]{3}}{\sqrt[3]{4}} \\ =\frac{\sqrt[3]{3}\cdot\sqrt[3]{4^2}}{\sqrt[3]{4}\cdot\sqrt[3]{4^2}} \\ =\frac{\sqrt[3]{3}\cdot\sqrt[3]{2^4}}{4^{\frac{1}{3}+\frac{2}{3}}} \\ =\frac{\sqrt[3]{3}\cdot2^{\frac{4}{3}}}{2^2} \\ =\frac{\sqrt[3]{3}\sqrt[3]{2}}{2} \\ =\frac{\sqrt[3]{6}}{2} \end{gathered}[/tex]Finally we obtain that the correct answer is the second option.